2016
DOI: 10.3390/ijms17122112
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Starch Degradation Related Genes in Postharvest Kiwifruit

Abstract: Starch is one of the most important storage carbohydrates in plants. Kiwifruit typically accumulate large amounts of starch during development. The fruit retain starch until commercial maturity, and its postharvest degradation is essential for consumer acceptance. The activity of genes related to starch degradation has, however, rarely been investigated. Based on the kiwifruit genome sequence and previously reported starch degradation-related genes, 17 novel genes were isolated and the relationship between the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
36
0
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 37 publications
6
36
0
1
Order By: Relevance
“…To understand the molecular mechanisms of kiwifruit ripening, biosynthetic genes and transcription factors have been identified, after manipulation of ethylene production (Atkinson et al, 2011), cell wall metabolism (Atkinson et al, 2009), starch degradation (Hu et al, 2016;Zhang et al, 2018a) and aroma formation (Nieuwenhuizen et al, 2015). To understand the molecular mechanisms of kiwifruit ripening, biosynthetic genes and transcription factors have been identified, after manipulation of ethylene production (Atkinson et al, 2011), cell wall metabolism (Atkinson et al, 2009), starch degradation (Hu et al, 2016;Zhang et al, 2018a) and aroma formation (Nieuwenhuizen et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To understand the molecular mechanisms of kiwifruit ripening, biosynthetic genes and transcription factors have been identified, after manipulation of ethylene production (Atkinson et al, 2011), cell wall metabolism (Atkinson et al, 2009), starch degradation (Hu et al, 2016;Zhang et al, 2018a) and aroma formation (Nieuwenhuizen et al, 2015). To understand the molecular mechanisms of kiwifruit ripening, biosynthetic genes and transcription factors have been identified, after manipulation of ethylene production (Atkinson et al, 2011), cell wall metabolism (Atkinson et al, 2009), starch degradation (Hu et al, 2016;Zhang et al, 2018a) and aroma formation (Nieuwenhuizen et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Kiwifruit is an ideal species to understand fruit ripening, as it is considered a typical climacteric fruit and also is more sensitive to ethylene than most other fruit. To understand the molecular mechanisms of kiwifruit ripening, biosynthetic genes and transcription factors have been identified, after manipulation of ethylene production (Atkinson et al, 2011), cell wall metabolism (Atkinson et al, 2009), starch degradation (Hu et al, 2016;Zhang et al, 2018a) and aroma formation (Nieuwenhuizen et al, 2015). Here, the regulatory roles of micro (mi)RNAs for kiwifruit ripening were studied via analysis of the sRNAome, degradome and transcriptome.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, several MYB TFs like FaMYB10 and FaEOBII, mediate the production of volatile compounds by targeting phenylpropanoid pathway genes during strawberry fruit ripening (Medina‐Puche et al ., , ). Similarly, in apple MdMYB1/10/73 modulate fruit organic acid accumulation by directly activating vacuolar transporters (Hu et al ., ,b, ). However, the involvement of MYB TFs in complex carbohydrate metabolism associated with fruit quality during ripening has not been well understood.…”
Section: Introductionmentioning
confidence: 97%
“…In addition, maltose excess protein (MEX1) and plastidic glucose transporter (pGlcT) transfer maltose and glucose to cytosol (Cho et al ., ). Many genes encoding these starch degradation enzymes have been isolated in kiwifruit (Hu et al ., ,b) and bananas (Gao et al ., ; Xiao et al ., ). Moreover, it has been shown that starch degradation in these fruits is highly complex and is mediated by the changes of starch degradation enzymes at transcript and protein levels (Gao et al ., ; Hu et al ., ,b; Xiao et al ., ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation